Prevalence of Self-Reported Prescription Opioid Use and Illicit Drug Use Among U.S. Adults: NHANES 2005–2016. Issue 1 (January 2022) - Gu, Ja K.; Allison, Penelope; Grimes Trotter, Alexis; Charles, Luenda E.; Ma, Claudia C.; Groenewold, Matthew; Andrew, Michael E.; Luckhaupt, Sara E.
Abstract : Objective: To estimate the self-reported prevalence of prescription opioid use and illicit drug use in the United States. Methods: Self-reported prescription opioid use and illicit drug use (mostly nonopioid) were obtained for adults and adult workers (NHANES 2005–2016). Results: Prevalence (95% CI) of prescription opioid use was 6.5% (6.0–7.0) (adults) and 4.1% (3.7–4.5) (workers). Prevalence of illicit drug use was 9.5% (8.8–10.1) (adults) and 10.2% (9.4–11.1) (workers). Among occupations, prevalence of prescription opioid use was highest in personal care (6.5%; 4.1–10.4) and healthcare practitioners (5.9%; 3.8–9.0); for illicit drug use, construction/extraction (18.0%; 15.1–21.3) and food preparation (15.8%; 12.5–19.7). Conclusion: The prevalence of prescription opioid use was elevated among some occupations. Judicious prescription strategies and targeted interventions are both needed. The prevalence of illicit drug use among certain occupational groups suggests the need to ensure access to therapy. Abstract : Supplemental Digital Content is available in the text